2010
DOI: 10.1039/c0cc03622f
|View full text |Cite
|
Sign up to set email alerts
|

Phosphine-mediated disulfide metathesis in aqueous media

Abstract: Dynamic carbohydrate systems have been efficiently generated through phosphine-mediated disulfide metathesis in aqueous media. The protein compatibility and binding features of the dynamic systems were demonstrated in situ using (1)H STD NMR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 38 publications
(2 reference statements)
0
17
0
Order By: Relevance
“…The healing process as such is based on disulfide bond re‐shuffling which can be triggered by mild temperatures, shear forces, reduction reactions, or UV‐irradiation. Nucleophilic reagents such as phosphine and thiol groups can further facilitate disulfide bonds scission. Recent developments have shown that elastomers with healing capabilities at room temperature can be developed by the metathesis of disulfide bonds in the absence of catalyst using aromatic disulfides .…”
Section: Introductionmentioning
confidence: 99%
“…The healing process as such is based on disulfide bond re‐shuffling which can be triggered by mild temperatures, shear forces, reduction reactions, or UV‐irradiation. Nucleophilic reagents such as phosphine and thiol groups can further facilitate disulfide bonds scission. Recent developments have shown that elastomers with healing capabilities at room temperature can be developed by the metathesis of disulfide bonds in the absence of catalyst using aromatic disulfides .…”
Section: Introductionmentioning
confidence: 99%
“…[14] As ac onsequence,e ach network is interconnected to and interdependentwith another network. Althoughd ynamic disulfide bonds are normally activated under basic conditions, [12d] they can also be elicited in the presence of phosphine- [15] or NHC-based [16] catalysts as well as under ultrasound, [17] grinding [18] and photoirradiation. [19] The photochemical exchange of dithioacetals has not been explored,h owever the photoactivation of their CÀSb ond has been exploited for addition of dithioacetals to alkenes [20] and for deprotection of dithioacetals.…”
mentioning
confidence: 99%
“…[6,12] The readily exchangeable-S ÀS-linkage [13] can be utilized in metathesis reactions to rapidlya ccess diversel ibraries of heterodimeric analoguesf rom as mall number of disulfide building blocks. [8,14] Several methods have been recentlyd eveloped to facilitate the disulfide metathesis reactions using phosphine catalysts [15] or mechano- [9a, 16] and photochemicalp rocesses. [17] However,i t is still an ongoing challenge to address the limitations in substrate scope,e quilibration time and the precision of these methods.…”
mentioning
confidence: 99%